OPTIMIZING THE UNDERSTANDING OF INTEGERS WITH AN ECONOMIC APPROACH TO IMPROVE THE MATHEMATICS LEARNING OUTCOMES OF SEVENTH GRADE STUDENTS AT MTS PSM SUGIHWARAS - Dewa, Angga Gama Kurnia; Palupi, Ragil Retno; Patmaningrum, Agustin (Sekolah tinggi ilmu ekonomi pemuda, 2025)
ABSTRACTIntegers are a fundamental topic in mathematics that are often considered abstract by students,especially at the junior high school level, which makes it difficult to understand the material. In fact,the concept of integers has many connections to everyday life, such as economic activities involvingprofit and loss in business, debts, and repayments. This study aims to examine the effectiveness ofthe economic approach in teaching integers on improving the mathematics learning outcomes ofseventh-grade students at MTs PSM Sugihwaras. The research method used is Classroom ActionResearch with 2 cycles. The research subjects were seventh-grade students in class VII-A at MTsPSM Sugihwaras, totaling 22 students. Out of a total population of 45 students in the seventh grade,through the implementation of economic-based contextual learning, students were invited tounderstand integers through simulations of simple economic activities. The results of the studyshowed that this approach was able to improve learning outcomes.